Pengembangan Media Display Flipchart Berbasis Komik pada Pembelajaran IPA Kelas IV SD Negeri 136 Palembang - Nopianti, Indri; Akhbar, M. Taheri; Aryaningrum, Kiki (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Development of Flipchart Display in Fourth Grade Science Learning at SD Negeri 136 Palembang. Media flipchart display a comic-based in science learning for class IV SD Negeri 136 Palembang which is valid and practical. This type of research and development uses (Research and Development) using the ADDIE model which consists of 5 stages, namely, 1) Analyze 2)Design, 3) Development, 4) Implementation, 5) Evaluation). The subjects in this study were 1media expert validator, 1 material expert validator, 1 linguist validator, and grade IV elementary school students totaling one to one as many as 3 students and a small group of 8 students. The data collection instruments were media validation sheets by validators, practical questionnaires from students and documentation. Based on the results of the research, the average assessment by media experts was 74%; material experts were 83.75%; and linguists were 71% with valid categories, and the results of student response questionnaires were one to one 78% small group of 80.75% in the practical category.